Inhaled iloprost for the treatment of patient with Fontan circulation - Yong Hyun Kim; Moon Hee Chae; Deok Young Choi (Korean Pediatric Society, 2014)
Decreased exercise capacity after Fontan surgery is relatively common and the failure of the Fontan state gradually increases with age. However, there is no further treatment for patients with Fontan circulation. Pulmonary vasodilation therapy is an effective method to solve this problem because pulmonary vascular resistance is a major factor of the Fontan problem. Inhaled iloprost is a chemically stable prostacyclin analogue and a potent pulmonary vasodilator. We experienced two cases of Fontan patients treated with inhaled iloprost for 12 weeks. The first patient was an 18-year-old female with pulmonary atresia with an intact ventricular septum, and the second patient was a 22-year-old male with a double outlet right ventricle. Fifteen years have passed since both patients received Fontan surgery. While the pulmonary pressure was not decreased significantly, improved exercise capacity and cardiac output were observed without any major side effects in both patients. The iloprost inhalation therapy was well tolerated and effective for the symptomatic treatment of Fontan patients.